MUC2 expression modulates immune infiltration in colorectal cancer - Raynaud, Christophe M.; Jabeen, Ayesha; Ahmed, Eiman I.; Hubrack, Satanay; Sanchez, Apryl; Sherif, Shimaa; Al-Shaibi, Ahmad A.; Lo, Bernice; Roelands, Jessica; Bedognetti, Davide; Hendrickx, Wouter (Frontiers in Immunology, 2025)
IntroductionColorectal cancer (CRC) is a prevalent malignancy with significant morbidity and mortality worldwide. A deeper understanding of the interaction of cancer cells with other cells in the tumor microenvironment is crucial to devise effective therapeutic strategies. MUC2, a major component of the protective mucus layer in the gastrointestinal tract, has been implicated in CRC progression and immune response regulation.MethodIn this study, we sought to elucidate the relationship between MUC2 expression and immune infiltration within CRC using in vitro models involving two well-established cell lines, HT-29 and LS-174T. By employing CRISPR-mediated MUC2 knockout, we investigated the influence of MUC2 on tumor immune infiltration and its interplay with T cells and NK cells enriched peripheral blood mononuclear cells (PBMCs) in 3D spheroid cultures.ResultsWhile MUC2 was more abundant in LS-174T cell line compared to HT-29, its knockout resulted in increased immune infiltration solely in the HT-29 cell line, but not in the LS-174T cell line. We revealed that the removal of MUC2 protein was compensated in LS-174T by the expression of other gel-forming mucin proteins (MUC6, MUC5B) commonly expressed in the gastrointestinal epithelium, while this was not observed in HT-29 cell line.ConclusionOur study is the first to demonstrate that MUC2 functions as a physical barrier to immune infiltration in colorectal cancer (CRC) in vitro. In HT-29 cells, MUC2 knockout increased immune infiltration, while in LS-174T cells, compensatory expression of other mucins (MUC6, MUC5B) maintained the barrier. These findings reveal the complexity of mucin biology in CRC and suggest that targeting mucin pathways could be a novel therapeutic approach.